Influence of the Load Inductance on the Turn-off Test for IGBT - TENG Yuan; QIN Rongzhen; YANG Xinzhu; LUO Xiang; XIAO Qiang (Kongzhi Yu Xinxi Jishu)
The load inductor in the IGBT dynamic test circuit (clamped inductive circuit) works as a current source. Therefore, the load inductance is considered to have no influence on the test results. In this paper, it is found that the IGBT turn-off parameters increase with the load inductance within limits, and this property is related to the device designs. With the analysis of device physics mechanism, it is found that the load inductance affects the voltage rise rate at turning-off, and thus affects the ratio of the hole current at turning-off.